Foam flow of oil-refrigerant R12 mixture in a small diameter tube - Poiate Jr., Edgard; Gasche, José Luiz [UNESP] (Associação Brasileira de Engenharia e Ciências Mecânicas - ABCM, 2006)
This paper presents an experimental investigation of the mineral oil ISO VG10-refrigerant R12 mixture flow with foam formation in a straight horizontal 3.22 mm ID, 6.0 m long tube. An experimental apparatus was designed to allow the measurement of both pressure and temperature profiles along the tube as well as the visualization of the flow patterns. Tests were performed at different mass flow rates, several refrigerant mass fractions at the inlet of the flow, and inlet mixture temperatures around 29.0 °C. At the inlet of the tube a liquid mixture flow was visualized. In this region, both temperature and pressure gradient were constant. As the flow proceeded towards the exit of the tube the pressure drop produced a reduction of the refrigerant solubility in the oil yielding to the formation of the first bubbles. Initially, small and few bubbles could be noticed and the flow behaved as a bubbly flow. Eventually, the bubble population increased and foam flow pattern was observed at the exit of the tube. Due to the large formation of bubbles, both the temperature and the pressure of the mixture were substantially reduced in this region. Visualization results also showed that both flow regimes (bubbly and foam) were intermittent.
Keywords: Oil-refrigerant mixture; foam flow; two-phase flow pattern; flashing flow